The European Policy for Liver Allocation in Patients Affected by Hepatocellular Carcinoma - Di Sandro, S; Ferla, F; Lauterio, A; Mangoni, I; De Carlis, R; Buscemi, V; De Carlis, L (Chirurgia, 2017)
The main goal of allocation system is to guarantee an equal access to the limited resource of liver grafts for every class of patients on the waiting list, balancing between the ethical principles of equity, utility, benefit, need, and fairness. The aim of this review was to analyze liver allocation policies among these organizations, focusing on HCC. The European area considered for this analysis included 6 macro-areas or countries, which are congregated from the same policy of liver sharing and allocation. By this definition, the 6 areas identified are: Centro Nazionale Trapianti (CNT) in Italy; Eurotransplant (Germany, the Netherlands, Belgium, Luxembourg, Austria, Hungary, Slovenia, and Croatia); Organizacion Nacional de Transplantes (ONT) in Spain; Etablissement francais des Greffes (EfG) in France; NHS Blood Transplant (NHSBT) in the United Kingdom and Ireland; Scandiatransplant (Sweden, Norway, Finland, Denmark, and Iceland); Romanian National Policy. Each identified area, as network for organ sharing in Europe, adopts a basic allocation system that consider a policy center oriented or patient oriented. Priorization of patients affected by HCC in the waiting list for deceased donors liver transplant worldwide is dominated by 2 main principles: urgency and utility. The main message of this review is the absence of a common organs allocation policy over the Eurpean countries. Despite that, long-term survival of the community of patients listed for transplant due to HCC results, however, highly acceptable in Europe and comparable to the long-term survial reported in the UNOS register